2022
DOI: 10.3390/foods11081152
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Survey of Phenolic Constituents Reported in Monofloral Honeys around the Globe

Abstract: The aim of this review is to provide a comprehensive overview of the large variety of phenolic compounds that have to date been identified in a wide range of monofloral honeys found globally. The collated information is structured along several themes, including the botanical family and genus of the monofloral honeys for which phenolic constituents have been reported, the chemical classes the phenolic compounds can be attributed to, and the analytical method employed in compound determination as well as countr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 179 publications
0
20
0
Order By: Relevance
“…However, it is a costly technique, both in terms of equipment and running costs, and it requires technical expertise for its operation and data analysis [ 57 ]. In light of these shortcomings, high-performance liquid chromatography (HPLC) coupled with diode array detection (DAD) appears to be the most commonly employed technique for the qualitative and quantitative analyses of phenolic compounds [ 1 , 8 , 16 , 58 ]. Although the set up of HPLC–DAD is relatively cheap and the analysis robust, the method nonetheless faces several disadvantages, such as i) compound identification is only based on retention times and associated UV spectra, which might not allow us to sufficiently discriminate between compounds of a very similar chemical nature, and ii) low detection and quantification limits when analysing complex matrices [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, it is a costly technique, both in terms of equipment and running costs, and it requires technical expertise for its operation and data analysis [ 57 ]. In light of these shortcomings, high-performance liquid chromatography (HPLC) coupled with diode array detection (DAD) appears to be the most commonly employed technique for the qualitative and quantitative analyses of phenolic compounds [ 1 , 8 , 16 , 58 ]. Although the set up of HPLC–DAD is relatively cheap and the analysis robust, the method nonetheless faces several disadvantages, such as i) compound identification is only based on retention times and associated UV spectra, which might not allow us to sufficiently discriminate between compounds of a very similar chemical nature, and ii) low detection and quantification limits when analysing complex matrices [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Figures S1–S15 and Tables S1–S14 summarise information, such as the identity, supplier, prepared concentration and HPTLC sample application of the standard compounds used to construct the database. Compounds were selected based on the findings of a comprehensive review of (mainly) phenolic compounds identified, to date, in honeys around the world [ 16 ]. The pool of standards was complemented with isomers of some of these compounds, compounds that were reported for other bee products (e.g., pollen and propolis) and other phenolic compounds available to the research team.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, most honeys harvested form beehives in Greek mainland and islands showed abundance in phenolics (flavonoids and phenolic acids), volatile compounds and trace metals that were seen to enhance its antimicrobial potency (Spilioti et al., 2014). For instance, thyme, fir, pine, citrus and orange blossom honey species showed the highest phenolic content (up to 300 mg kg −1 ), compared to other indigenous honeys (Lawag et al., 2022). The pH thereof was found to range between 3.4 (orange blossom) and 5.31 (fir honey), while the free acidity ranged between 15.44 meq kg −1 (thyme) and 50.75 meq kg −1 (fir and pine).…”
Section: Introductionmentioning
confidence: 99%